2004
DOI: 10.1159/000083598
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Palliation and Nutritional Support in Advanced Gastric Cancer

Abstract: Most of the patients with advanced gastric cancer have incurable disease at presentation and require palliative treatment to reduce symptoms as vomiting, nausea and inability to eat. Treatment options are palliative surgery and endoscopic techniques. Insertion of self-expanding metal stents is nowadays a well-established method of treating biliary and esophageal strictures and is also effective in gastric tumors. The indication and application technique are described in this review. In addition, enteral nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
1
3
0
1
Order By: Relevance
“…A recent study by Matsumoto et al in patients with both duodenal and biliary stents reported 26 % and 41 % biliary stent dysfunction rates at 3 and 6 months, respectively, which was like the reintervention rate we reported 7 . Tumor ingrowth into the biliary stent, causing recurrent biliary obstruction and/or cholangitis, was the most likely cause of stent dysfunction in these patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent study by Matsumoto et al in patients with both duodenal and biliary stents reported 26 % and 41 % biliary stent dysfunction rates at 3 and 6 months, respectively, which was like the reintervention rate we reported 7 . Tumor ingrowth into the biliary stent, causing recurrent biliary obstruction and/or cholangitis, was the most likely cause of stent dysfunction in these patients.…”
Section: Discussionsupporting
confidence: 86%
“…MBO and duodenal obstruction are often seen as complications of pancreatic, duodenal or metastatic cancers. Dorman et al reported as many as 60 % of patients with advanced gastroduodenal and pancreatic malignancies develop biliary obstruction after duodenal obstruction, and thus, may already have a duodenal stent in place 7 . Our study represents the largest single-center cohort of patients with malignant biliary and duodenal obstruction in which transpapillary biliary stenting was attempted, in the presence of a preexisting duodenal stent.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 30% of patients with pancreatic and more than 50% of patients with gastric cancer already have incurable disease, with distressing symptoms of gastric outlet obstruction at the time of presentation, and require effective palliation. The principal objective of palliative treatment in this situation is the resolution of obstructive symptoms and resumption of oral intake [19-21]. …”
Section: Discussionmentioning
confidence: 99%
“…Uma abordagem comum para direcionar a desnutrição e a perda de peso é o aumento de ingestão calórica com suplementos orais, para garantir os requerimentos diários em casos de baixa ingestão alimentar, independentemente dos motivos 7,10,26,33 . Essa conduta pode ter menos riscos e menor custo que a nutrição artificial 36 , entretanto não há precisão nos poucos estudos disponíveis acerca de seu monitoramento, freqüência, quantidade e eficácia 25,26,28,33 .…”
Section: Comunicação: Fundamental No Cuidado Ao Pacienteunclassified